2014
DOI: 10.1111/jop.12185
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco increases aneuploidy in oral HPV16 E6/E7‐transformed keratinocytes in vitro

Abstract: The effect of STE varied in the cell lines studied. STE2 increased significantly the proportion of aneuploid cells in HPV-positive oral keratinocytes, but not HPV16 E6/E7 expression. This indicates that tobacco products may enhance the effects of HPV 16 and the risk of DNA aneuploidy increasing risk to malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Probably, there is a correlation between smoking and HPV 16 infection on the one hand and oropharyngeal squamous cell carcinoma, on the other [ 32 ]. Merne et al [ 33 ] suggest a possible synergy between tobacco components and viral oncogenes, especially HPV16 E6/E7 in transformation of oral epithelial cells. Studies by Haukioja et al [ 34 ] found out that smoking is a risk factor for a persistent oral HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, there is a correlation between smoking and HPV 16 infection on the one hand and oropharyngeal squamous cell carcinoma, on the other [ 32 ]. Merne et al [ 33 ] suggest a possible synergy between tobacco components and viral oncogenes, especially HPV16 E6/E7 in transformation of oral epithelial cells. Studies by Haukioja et al [ 34 ] found out that smoking is a risk factor for a persistent oral HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of HPV-positive patients with oropharyngeal cancer, the risk of death increased significantly with pack-years of tobacco smoking [ 70 ]. The risk of neoplastic transformation is increased by tobacco products, which could potentiate the effects of HPV 16 [ 71 ], and smoking significantly increased the risk of persistent oral HPV infection, which, in turn, might increase the risk of cancer [ 72 ]. Head and neck epithelium is often exposed to tobacco carcinogens and might interact with HPV to stimulate neoplastic lesions [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV detection and identification of subtypes were performed by GenoFlow HPV (Human Papillomavirus) Array Test Kits (DiagCor Bioscience Inc., Hong Kong) which use biotin-labeled primers, specific probes, PCR and "flow-through" hybridization technology, which allows detection of 33 common HPV subtypes. The following are considered highrisk (16,18,31,33,35,39,45,51,52,53,56,58,59,66,68,73,82) and low-risk (6,11,26,40,42,43,44,54,55,57,61,70,71,72,81,84) subtypes based on their phylogenetic and epidemiological criteria and the biological niche. The extracted DNA was mixed with PCR reagent mix and DNA Taq Polymerase provided with the kit and amplified using a Mastercycler Personal Thermal Cycler (Eppendorf, Hamburg, Germany) according to the manufacturer's protocol.…”
Section: Hpv Detection and Type Determinationmentioning
confidence: 99%
“…There is increasing epidemiological evidence to suggest synergism between tobacco carcinogens and HPV infection in cancer induction [16][17][18][19][20]33,34]. Furthermore, synergism between tobacco carcinogens and hr-HPV was also observed in in vitro experiments using human cells derived from cervical, lung, and oral cancers [35][36][37][38][39][40][41]. AP, a typical flavonoid with low toxicity and multiple beneficial bioactivities, has been evaluated as a promising candidate for chemoprevention against a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%